Active control of thermal buckling and vibration for a sandwich composite laminated plate with piezoelectric fiber-reinforced composite actuator facesheets. (October 2019) - Li, Jinqiang; Li, Fengming; Narita, Yoshihiro
The present paper is concerned with the active control of thermal buckling and vibration of a sandwich composite laminated plate with piezoelectric fiber-reinforced composite actuator facesheets in a thermal environment. An active temperature feedback control strategy is proposed for the thermal buckling of the composite sandwich plate. The results of numerical simulations show that the piezoelectric actuator can significantly improve the thermal buckling characteristics of the composite plates. The influence of the active thermal buckling control gain on the damping ratio and natural frequency of the structure is also investigated. From the numerical results it is observed that the active thermal buckling control with temperature feedback gain can not only enlarge the critical buckling temperature but can also reduce the resonant amplitude of the structure. Furthermore, the optimization problem is studied and it is found that the critical buckling temperature can be optimized by varying the fiber orientation in the piezoelectric fiber-reinforced composite layer. The active thermal buckling control method presented in this paper working in combination with the vibration control strategy can significantly improve the stability of the laminated composite plates. The present study will be useful for designing laminated composite structures used in the thermal environment.